Advanced techniques for estimation of the tensile fracture toughness of adhesive joints (Fracture and Structural Integrity, 2014)
Adhesive bonding has become more efficient in the last few decades due to the adhesives developments, granting higher strength and ductility. As a result, adhesives are being increasingly used in industries such as the automotive, aerospace and construction. Thus, it is highly important to predict the strength of bonded joints to assess the feasibility of joining during the fabrication process of components (e.g. due to complex geometries) or for repairing purposes. When using the Finite Element Method with advanced propagation laws, the tensile (Gnc) and shear (Gsc) fracture toughness of adhesive joints must be determined with accuracy. Several conventional methods to obtain Gnc and Gsc exist in the literature, mainly based on Linear Elastic Fracture Mechanics (LEFM). The J-integral technique is accurate to measure these parameters for adhesives with high ductility. In this work, the J-integral is used to obtain Gnc by the Double-Cantilever Beam (DCB) test. An optical measurement method is developed for the evaluation of the crack tip opening and adherends rotation at the crack tip during the test, supported by a Matlab® sub-routine for the automated extraction of these quantities. As output of this work, an optical method that allows an easier and quicker extraction of the parameters to obtain Gnc than the available methods is proposed (by the J-integral technique) and some results are presented regarding joints with different geometry and adherend material.
Keywords: Fibres